Spanish Intimate Partner Violence Survivors Help-Seeking Strategies Across the Life Span - Sanz-Barbero, Belén (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) and its associated factors may vary according to women?s age. In this study, we analyze the effect of age on help-seeking behavior and the associated factors among women exposed to IPV in Spain. Using the Spanish Macrosurvey on Gender Violence of 2014, we analyzed the frequency of help-seeking behavior (police report, formal resources, and informal networks of support) in women who were exposed to lifetime physical/sexual or fear-based IPV (n = 1,567 women). We used Poisson regression models to obtain variables associated with support resources. The analysis was carried out in three age groups: young women (16?29 years old), adults (30?49 years old), and older women (50 years and over). Our results show that informal support networks are the most used resource by all women?s age groups. The probability of filing a police complaint increases among women exposured to physical IPV (PRadult : 1.58; ?PRelder : 2.17 ). The probability of using formal resources decreased among older women with low family socioeconomic status (PR: 0.80) and in adult women exposed to sexual IPV (PR: 0.78), and increased among young women and adult Spanish women (PRyoung: 1.65; PRadult: 1.34). The use of informal support networks increased among adult women with physical and mental health effects (PR: 1.22). In older women use of informal support networks was associated with the type of IPV (PRphysical: 1.14; PRsexual: 0.88). The presence of minors who witnessed IPV increased help-seeking behavior among adult and older women.In conclusion, the knowledge of the differences in help-seeking strategies by women in different age groups could contribute to designing strategies to promote women?s ability to seek formal help when exposed to IPV.